2010
DOI: 10.1253/circj.cj-09-0486
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Endostatin/Collagen XVIII Deteriorates Left Ventricular Remodeling and Heart Failure in Rat Myocardial Infarction Model

Abstract: Neutralization of endostatin worsens the symptoms and outcomes of MI in a rat model. The results imply that endogenous endostatin/collagen XVIII may suppress aberrant LV remodeling and heart failure after MI. (Circ J 2010; 74: 109 - 119).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 33 publications
(53 reference statements)
1
54
0
Order By: Relevance
“…13,14,17- 21 We previously demonstrated that MMP-9 expression increases in fibrillating atrial tissue, which may contribute to the atrial structural remodeling of AF. 22 However, the mechanism of the increase in MMP-9 expression in fibrillating atrial tissue remains unknown.…”
Section: Ogi H Et Almentioning
confidence: 99%
“…13,14,17- 21 We previously demonstrated that MMP-9 expression increases in fibrillating atrial tissue, which may contribute to the atrial structural remodeling of AF. 22 However, the mechanism of the increase in MMP-9 expression in fibrillating atrial tissue remains unknown.…”
Section: Ogi H Et Almentioning
confidence: 99%
“…Serum endostatin level in the coronary circulation was upregulated in coronary heart disease (Mitsuma et al, 2007). Expression of endostatin increases in the heart tissues of experimental cardiac disease models, such as myocardial infarction (Isobe et al, 2010;Qipshidze et al, 2012) and pressure overload-induced cardiac hypertrophy (Givvimani et al, 2011;Nikolova et al, 2012). In addition, antiendostatin antibody worsened cardiac remodeling after myocardial infarction (Isobe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular matrix plays an important role in left ventricular (LV) remodeling, and changes in expression patterns of extracellular matrix proteins may contribute to HF progression. Experimental data demonstrate abundant expression of the anti-angiogenic factor endostatin in cardiac tissue, suggesting a potential role in myocardial remodeling during HF [1]. Furthermore, Gouya et al [2] recently demonstrated that high serum endostatin levels were associated with all-cause mortality in a relatively small study population of HF patients.…”
Section: Introductionmentioning
confidence: 99%